Simple molecular engineering of glycol nucleic acid: progression from self-pairing to cross-pairing with cDNA and RNA - Bose, Tanaya; Kumar, Vaijayanti A. (Bioorganic & Medicinal Chemistry, 2014)
The acyclic chiral nucleic acid analogue, Glycol Nucleic Acid (GNA), displayed exceptional structural simplicity and atom economy while forming self-paired duplexes, using canonical Watson-Crick base pairing. We disclose here that the replacement of phosphodiester linker in GNA with somewhat rigid and shorter carbamate linker in Glycol Carbamate Nucleic Acid (GCNA) backbone allows unprecedented stability to the antiparallel self-paired duplexes. The R-GCNA oligomers were further found to form cross-paired antiparallel duplexes with cDNA and RNA following Watson-Crick base pairing. The stability of cross-paired GCNA: DNA and GCNA: RNA duplexes was higher than the corresponding DNA: DNA and DNA: RNA duplexes. The chiral (R) and (S) precursors were easily accessible from naturally occurring L-serine. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Acyclic chiral nucleic acid; Cross-pairing; GCNA; GNA; Self-pairing